Effect of Low Positive End of Treatment Viral Load with Direct-Acting Antiviral Therapy on Sustained Virologic Response - Vabhave Pal; Nirupama Ancha; Jena Mann; Apurva A. Modi (Canadian Journal of Gastroenterology and Hepatology)
Background. Direct-acting antivirals (DAAs) are highly effective treatments against hepatitis C virus (HCV), with sustained virologic response (SVR) rates of 93–100% against all genotypes. In most patients, viral load (VL) becomes undetectable four weeks into treatment, but rarely a low positive VL may be observed at the end of treatment (EOT). This study was conducted to determine the effect of low positive EOT VLs with DAA therapies on SVR at 12 and 24 weeks. Methods. A retrospective chart review was conducted from January 2014 to December 2018 on 1256 HCV patients of all genotypes (1–6) who had received DAA therapy at two large hepatology referral centers. Baseline demographic data, along with VL at week four, EOT, and SVR12/24 time points were collected for patients that had positive EOT VL. Treatment outcome for any patient with positive EOT VL was noted. Results. Eight out of 1256 patients treated with varying DAA therapies were observed to have low positive EOT VLs ranging from <15 to 235 IU/mL. One patient had a negative EOT VL, but 23 IU/mL at week four after EOT. All eight patients who had low positive EOT VLs and one patient who had a low positive VL at four weeks after EOT achieved SVR at weeks 12 and 24. One of the eight patients had cirrhosis. The majority of patients were genotype 1a. Conclusion. In the DAA treatment era, low levels of detectable HCV RNA at EOT does not predict treatment failure.